Challenges and Barriers of Humanitarian Hygiene Items Management in Recent Disasters in Iran. (12th May 2023) - Adibi Larijani, Haleh; Moslehi, Shandiz; Barghi Shirazi, Fahimeh; Pashaee Asl, Yosef; Alikhani, Afshin; Fatemi, Farin
Abstract: Objective: The provision and continuation of the basic needs of affected communities, including water, food, and shelter remain the most important priorities in responding to disasters. In this regard, this study sought to investigate the management challenges of humanitarian hygiene items in recent disasters in Iran. Methods: This qualitative study was conducted through a semi-structured interview. Nineteen participants with different experiences, roles, and responsibilities in the recent disaster of Iran and experiences of various events in the national and international arenas were included in the study. A thematic analysis was used, and an initial conceptual framework was defined based on the study aim. The relationship between the components was compared and interpreted in this framework and the main and subthemes were extracted accordingly. Results: Six main themes and 21 subthemes were extracted based on the results. The main challenges in recent disasters were the lack of protocols and standard guidelines, inappropriate selection of items in each hygiene kit, the lack of standard distribution of hygiene kits, and the lack of attention to the affected population's culture. Conclusions: Overall, it is necessary to define a system for preparation, supply, storage, and timely distribution of hygiene. Finally, it is suggested that an organization should be appointed for this purpose.